How Sweet the Ground: The Metaphysical Vision of Michael Marker - Rocha, Samuel D. (Journal of Contemporary Issues in Education, 2023)
Through this essay, Rocha seeks to describe and honour Michael Marker’s signature notion of the “metaphysical demand” within his more well-known historical and anthropological work on the agentic notion of place. The essay begins by noting the difficulty of this essay due to the “unwritability” of Marker, in allusion to Mellvile’s character, Bartleby, and Garcia Marquez’ssense of Latin America’s solitude. Then, after hermeneutic clarifications that resist reading this essay as a eulogy, the essay proceeds biographically reaching the intimate friendship between Rocha and Marker. These biographical confessions lead to Marker’s ideas, rooted in (and progressing from) Vine Deloria Jr’s critical understanding of the Indigenous philosophy of space, which proceed into a record of correspondence where Marker shares his idea of the metaphysical demand. The essay closes in a series of impressionistic anecdotes that contain key elements in Marker’s approach to his life and thought. A key element is Marker’s practice as a folk musician and his collaborative work with the author in the improvised composition of a track on claw-hammer and bluegrass banjo. From these memorial movements, Marker’s notion of the metaphysical demand of place, a voice that speaks through a calcified andlayered modern reality, is left unfinished, as he left it, to be heard and continued in work to follow.